MARKETING STRATEGY ANALYSIS AGENT BANKING MITRA TEPAT AT PT BANK TEPAT NASIONAL SYARIAH AS NEW BUSINESS OPPORTUNITY - Utaminingsih S, Theresia
In the contemporary financial landscape, financial inclusion emerges as a fundamental aspect of development strategies, crucial for both individual prosperity and macroeconomic growth. However, The World Bank's 2017 Global Findex database paints a sobering picture of this reality, highlighting that approximately 1.7 billion adults worldwide remain alienated from essential banking services, a consequence of multifaceted barriers. Indonesia, with its unique financial ecosystem characterized by the concurrent expansion of both conventional and Sharia banks, epitomizes this global challenge. Despite the impressive growth of the banking sector, reaching 31,000 units from 115 banks in 2018, the country still grapples with issues of limited banking literacy and accessibility for its citizens. In response, the Financial Services Authority (OJK) launched the 'LAKU PANDAI' initiative in 2015. This ambitious program harnesses the power of technology and external banking partnerships, endeavoring to deliver simplified and accessible banking services. Its primary goal is to diminish the financial inclusivity gap, fostering economic equality between Indonesia's rural and urban regions. A notable participant in this initiative is Bank Tepat Nasional Syariah (BTNS), which embraced the 'LAKU PANDAI' program through the introduction of "WOW! iB Agent" in 2015. This move aligned with BTNS's commitment to expanding growth opportunities across millions. However, BTNS's journey in agent banking encountered an unexpected paradox: the proliferation of Mitra Tepat (MT) or agent iii banking did not correspond with an increase in total transactions, but rather a marked decrease. This study aims to unravel the complexities surrounding the relationship between MT Growth and Transaction Decline at BTNS, seeking to understand the internal factors driving this decline and formulate effective marketing strategies for transaction augmentation. Employing a sequential and integrative research methodology, the study leverages a combination of SWOT, Porter's Five Forces, and PESTLE analyses to dissect internal and external factors. In-depth interviews with key stakeholders, including bank agents, customers, and managers, offer rich qualitative insights, complemented by a comprehensive desk study of existing literature and data. A subsequent quantitative survey targets a broader population sample to validate the findings and test hypotheses using Partial Least Squares Structural Equation Modeling (PLS-SEM). The qualitative analysis uncovers themes such as Innovative Agent Banking, Digitalization in Agent Banking, Popular Products and Agent Usage, Marketing Strategy, Opportunity in Agent Banking Development, Competition in Agent Banking Industry, Challenges in Business, Bank Support, Constraint in Implementing Marketing Strategies, Agent Marketing Strategy, The Influence of Digitalization, Benefits for Agents, Challenges in Implementation, Marketing Strategy Effectiveness, The Role of Digitalization in Marketing, Difficulties in Marketing, Approaches in Marketing Strategy. Following that, the quantitative analysis reveals that Communication (C), Customer Preferences (CP), and Products (P) significantly influence Relationship Marketing (RM), which in turn impacts Profitability (PR). Interestingly, the study finds that Market Structure (MS) does not have a significant effect on RM. A notable discovery is that Service Quality's (SQ) impact on RM, while statistically significant, presents a negative coefficient. Additionally, the study conducts a mediation analysis, uncovering that RM functions as a complementary partial mediator in the pathways from C to PR and from P to PR. However, an unexpected result emerges in the context of SQ, where its path coefficient consistently displays a negative value across all effects, iv indicating a possible false negative. This study recommends that PT BTNS intensify its focus on refining communication strategies, aligning product innovation with customer preferences, and thoroughly reassessing its service quality framework. These measures are pivotal in enhancing the bank's profitability and consolidating its competitive stance in the market, thus contributing significantly to the broader objective of financial inclusion in Indonesia.